PERBAIKAN PROSES PERAKITAN CASE ASSEMBLY FRONT WITH WATER PUMP AND OIL PUMP PADA PERUSAHAAN AUTOMOTIVE DI KARAWANG - Muhamad Sayuti (Lembaga Penelitian dan Pengabdian pada Masyarakat, Universitas Buana Perjuangan Karawang, 2020)
This research was conducted on companies engaged in the automotive sector. Many automotive component products are produced by this company, one of which is the case assembly front with water pump and oil pump. There are several elements that can be observed in the assembly process of the case assembly front with water pump and oil pump, starting from the number of man power, SOP (Standard Operational Procedure), assembled components, and so on. In the assembly process, there are several things that become obstacles, both in terms of product quality or from the constraints of the machines used. The case assembly front with water pump and oil pump has its own standard time or cycle time to meet customer demands. The production process for the case assembly front with water pump and oil pump still creates NG products which cannot be forwarded to the next process. The suggestion to increase the number of workers in the 004 line assembly, which is to 4 workers, can cause productivity to decrease from 0.85% to 0.81%. However, production capacity increased by 27% from the previous.